AC CALORIMETRY OF C-60 SINGLE-CRYSTALS - CHUNG, M; WANG, YQ; BRILL, JW; XIANG, XD; MOSTOVOY, R; HOU, JG; ZETTL, A (AMERICAN PHYSICAL SOC, 1992)
We have measured the (effective) specific heat of single crystals of C60 using ac calorimetry. For an fcc crystal prepared by sublimation, there is a sharp hysteretic lambda-shaped anomaly at 260 K, reflecting a latent heat spread over 3 K, similar to what is observed in powders using differential scanning calorimetry. There is also a discontinuity of 11.6R in the specific heat. For orthorhombic crystals prepared by slow evaporation from a toluene-hexane solution, a nonhysteretic, apparently second-order, transition is observed at 239 K. There is a peak in the specific heat consistent with a transition entropy of R ln12.
Keywords: HEAT